Crystalline-amorphous composite self-supporting material as well as preparation method and application thereof

By growing crystalline Cu-CuS2 microsheets on foam nickel substrate and growing amorphous NiCoS nanospheres on their surfaces, forming a composite structure, the problems of low catalytic activity and poor stability of non-precious metal electrocatalysts are solved, and efficient electrocatalytic hydrogen evolution performance and good stability are achieved.

CN119593009APending Publication Date: 2025-03-11GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510045949.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing non-precious metal electrocatalysts have problems with low catalytic activity, poor stability and complex process, especially the powdered catalysts are prone to fall off, resulting in reduced stability.

Method used

By growing crystalline Cu-CuS2 microsheets on foam nickel substrates and growing amorphous NiCoS nanospheres on their surfaces, a composite structure is formed, and Cu-CuS2 is coated with amorphous NiCoS to improve stability, and the interface electronic structure is adjusted through synergistic action to improve electrocatalytic performance.

Benefits of technology

It is realized that when the current density is 10mA·cm-2 in the range of 0--1.2V, the overpotential is 39-42mV, the Tafel slope is 130-136mV·dec-1, and the current retention rate is 95-98% under the 24-hour cycle time, which significantly improves the stability and electrocatalytic performance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593009A_ABST
    Figure CN119593009A_ABST
Patent Text Reader

Abstract

The invention discloses a crystalline-amorphous composite self-supporting material which is prepared by the following steps: taking foamed nickel NF as a substrate, taking copper sulfate pentahydrate, urea and ammonium fluoride as raw materials for hydrothermal reaction, obtaining NF / Cu-Cu2O through a hydrothermal method, then taking nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea as raw materials for electrodeposition, and preparing NF / Cu-CuS2 / NiCoS through an electrochemical deposition method; the NF is used as a self-supporting framework; cu-CuS2 is of a flaky hydrangea structure, the diameter of the Cu-CuS2 is 10 microns, NiCoS is of a nano spherical structure, and the diameter of the NiCoS is 10 nm; niCoS nanospheres grow on the sheet layer of the hydrangea structure; cu and CuS2 are in a crystalline state, and NiCoS is in an amorphous state. The preparation method comprises the following steps: 1, preparing NF / Cu-Cu2O; and 2, the NF / Cu-CuS2 / NiCoS is prepared. When the composite material is used as a hydrogen evolution catalyst material, the overpotential is 39-42 mV and the Tafel slope is 130-136 mV.dec-1 within the range of 0-1.2 V and when the current density is 10 mA. Cm <-2 >; and under the conditions that the current density is 10mA. Cm <-2 > and the cycle time is 24h, the current retention rate is 95-98%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to a crystalline-amorphous composite self-supporting material and a preparation method and application thereof. Background Art

[0002] In hydrogen production technology, the traditional electrocatalyst for electrocatalytic hydrogen evolution is precious metal materials. However, precious metal materials have the problems of high cost and scarce resources. When non-precious metals are used as hydrogen evolution catalysts, there are problems of low catalytic activity and poor stability.

[0003] In order to solve the problem of poor catalytic performance of non-precious metal catalysts due to limited catalytic active sites, their hydrogen evolution performance can be improved by regulating their composition and surface properties. For example, the existing literature 1 (Zhang L, Shen S, Zhang J, et al. Interlayer Spacing Regulation of Molybdenum Selenide Promotes Electrocatalytic Hydrogen Evolution in Alkaline Media [J]. Small Methods, 2022.) uses sodium molybdate dihydrate, cobalt chloride hexahydrate and ammonium fluoride as raw materials, obtains Co-Mo precursor by hydrothermal method, and then calcines it in a muffle furnace to obtain CoMoO 4 Then, selenium powder is used as raw material and annealed in a tubular furnace to obtain CoSe 2 / MoSe 2 The technical solution achieves a current density of 10 mA cm -2 Under the condition of , the overpotential is only 119mV. 2 / MoSe 2 As a powder catalyst, CoSe 2 / MoSe 2 After being uniformly dispersed in a solution made of Nafion, isopropanol and ethanol, it is coated on a glassy carbon electrode for hydrogen evolution reaction. That is, this technical solution has the problems of complex process, low content of active substances, and easy falling off of powdery substances.

[0004] In order to solve the problems of complex process and easy detachment of powdered non-precious metal hydrogen evolution catalysts, the active material can be directly grown on the substrate to form a self-supporting material to solve the problems caused by the need. For example, existing document 2 (Liang Y, Zhang L, Liu Q, et al. Amorphous Co-P Film: an Efficient Electrocatalyst for Hydrogen Evolution Reaction in Alkaline Seawater [J]. European Journal of Inorganic Chemistry, 2022.) uses nickel foam as a substrate, cobalt sulfate heptahydrate, sodium citrate, and sodium hypophosphite as raw materials, and prepares Co-P / NF by electrodeposition. This technical solution obtains a current density of 10 mA cm -2 Under the condition of , the overpotential is only 64mV. However, since this technical solution directly uses amorphous materials as electrocatalytic hydrogen evolution materials, amorphous materials have the problem of slow electron transmission rate inside the material, that is, poor conductivity, and amorphous materials are in a thermodynamically unstable state and have a tendency to transform into a crystalline state, that is, the material itself has a problem of poor stability.

[0005] For example, the existing document 3 (Lin Z, Zhou Y, Fu J, et al. Ultrahigh activity of molybdenum / vanadium-doped Ni-Co phosphides nanoneedles based on ion-exchange for hydrogen evolution at large current density [J]. Journal of Colloid and Interface Science, 2021.) uses nickel foam as the substrate and cobalt nitrate hexahydrate as the raw material to prepare the NiCo precursor by molten salt decomposition method, which is then immersed in sodium molybdate solution to obtain Mo-NiCo precursor, and then sodium hypophosphite is used as the raw material to obtain Mo-NiCoP / NF by tubular furnace annealing. This technical solution obtains a current density of 100 mA cm -2 Under the condition of , the overpotential is only 144mV. This technical solution uses crystalline materials as electrocatalytic hydrogen evolution materials. The active materials themselves have high stability. However, the crystalline materials have the problem of fewer active sites. In addition, the Mo-NiCoP / NF nanoneedles obtained by this technical solution will be in direct contact with the electrolyte during the hydrogen evolution reaction. Therefore, after a long reaction time, there is still a problem of significantly reduced stability due to catalyst shedding.

[0006] In order to solve the stability problem caused by direct contact between the active material and the electrolyte, a composite structure can be constructed with the outer layer material as a protective layer to prevent the inner layer material from falling off and being oxidized. For example, existing literature 4 (Ha Q, Gultom N, Silitonga M, et al. Novel core-shell structure of Ni 3 S 2 @LiMoNiO x (OH) y Using nickel foam as the substrate and lithium chloride, molybdenum chloride, thioacetamide and urea as raw materials, Ni nanorod arrays were prepared by a one-step hydrothermal method. 3 S 2 @LiMoNiO x (OH) y The technical solution achieves a current density of 10 mA cm -2 Under the condition of , the overpotential is only 57mV. Although the technical solution constructs a composite structure, due to the one-step hydrothermal preparation process, the inner and outer layers of the material are both crystalline materials, that is, the problem of low active sites cannot be solved.

[0007] Therefore, according to existing literature,

[0008] The characteristics of crystalline materials are that the crystal structure is conducive to the directional movement of electrons in the lattice, the electron conduction path is regular, the conductivity is good, and the standardized lattice structure can enhance the structural stability of the material. However, there is a problem of fewer active sites.

[0009] The characteristics of amorphous materials are that they have rich active sites and electronic structures for electrocatalytic hydrogen evolution due to their long-range disorder. However, they have problems with poor conductivity and poor stability.

[0010] Therefore, the current technical problem that needs to be solved when using non-precious metal catalysts as electrocatalytic hydrogen evolution materials is that when constructing a composite structure, it is impossible to construct a composite material that combines amorphous and crystalline states. Summary of the invention

[0011] The purpose of the present invention is to provide a crystalline-amorphous composite self-supporting material and its preparation method and application. The basic technical principle of the present invention is to use nickel foam as the base material, firstly, grow a Cu-Cu composite with a crystalline structure and a hydrangea structure on NF by hydrothermal reaction. 2 O, and then, by electrochemical deposition, Cu-Cu 2 O sulfidation to obtain Cu-CuS 2 At the same time, in Cu-CuS 2 Nano-spherical NiCoS with an amorphous structure is grown on the surface, thereby constructing a crystalline-amorphous composite structure;

[0012] Among them, Cu-CuS 2 The hydrangea-shaped microsheets provide a large number of active sites for the growth of NiCoS nanospheres and reduce the agglomeration of NiCoS nanospheres.

[0013] At the same time, by coating Cu-CuS with amorphous NiCoS 2 , to prevent Cu-CuS 2 The shedding of the material can improve the cycle stability;

[0014] In addition, Cu-CuS 2 The synergistic effect between amorphous NiCoS and crystalline Cu-CuS 2 Combined with tuning the electronic structure of the interfacial sites, the electrocatalytic performance is improved.

[0015] Therefore, NF / Cu-CuS 2 / NiCoS has the advantages of both crystalline and amorphous materials, that is, it has good conductivity, good stability and abundant active sites.

[0016] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:

[0017] A crystalline-amorphous composite self-supporting material, with nickel foam NF as the substrate, copper sulfate pentahydrate, urea and ammonium fluoride as the raw materials for hydrothermal reaction, and NF / Cu-Cu 2 O, and then nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea were used as raw materials for electrodeposition, and NF / Cu-CuS was prepared by electrochemical deposition. 2 / NiCoS;

[0018] The NF acts as a self-supporting framework; Cu-CuS 2 The microstructure is a hydrangea-like structure with a diameter of 10 μm, that is, the hydrangea layer is composed of Cu-CuS 2The micron sheets are composed of NiCoS nanospheres with a diameter of 10nm. NiCoS nanospheres grow on the hydrangea-structured sheets.

[0019] Moreover, Cu and CuS 2 It is crystalline, and NiCoS is amorphous.

[0020] A method for preparing a crystalline-amorphous composite self-supporting material comprises the following steps:

[0021] Step 1, NF / Cu-Cu 2 The preparation of CuO comprises the following steps: firstly, copper sulfate pentahydrate, urea and ammonium fluoride are dissolved in deionized water to obtain a hydrothermal reaction solution in a certain amount ratio of copper sulfate pentahydrate, urea and ammonium fluoride; then, under certain conditions, nickel foam NF is immersed in the hydrothermal reaction solution for hydrothermal reaction; after the hydrothermal reaction is completed, nickel foam loaded copper / cuprous oxide is obtained by washing and drying, which is referred to as NF / Cu-CuO. 2 O;

[0022] In the step 1, the molar ratio of copper sulfate pentahydrate, urea and ammonium fluoride is 2:10:5;

[0023] In step 1, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 110-130° C., and the hydrothermal time is 4-6 hours;

[0024] In the step 1, the nickel foam needs to be washed and dried before use. The specific washing and drying conditions are: washing the nickel foam with acetone, hydrochloric acid, deionized water and anhydrous ethanol in sequence, and drying at a drying temperature of 60° C. after washing;

[0025] Step 2, NF / Cu-CuS 2 Preparation of NF / Cu-Cu 2-NiCoS: First, nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea are dissolved in deionized water to obtain an electrodeposition solution in a certain amount ratio of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea; then, under certain conditions, the NF / Cu-Cu 2-NiCoS obtained in step 1 is added to the solution. 2 O is immersed in an electrochemical deposition solution for electrochemical deposition. After the electrochemical deposition is completed, it is washed and dried to obtain a crystalline-amorphous composite self-supporting material, referred to as NF / Cu-CuS 2 / NiCoS;

[0026] In the step 2, the molar ratio of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea is 2:4:3:8;

[0027] In step 2, the electrochemical deposition condition is that the current density is 90-100 mA·cm -2, electrodeposition time 10-20min.

[0028] When the crystalline-amorphous composite self-supporting material is used as a hydrogen evolution catalyst material, the current density is 10mA·cm in the range of 0-1.2V. -2 When the overpotential is 39-42mV, the Tafel slope is 130-136mV·dec -1 ;

[0029] At a current density of 10 mA cm -2 , under the condition of a cycle time of 24h, the current retention rate is 95-98%.

[0030] The technical effects of the present invention have been tested experimentally, and the specific contents are as follows:

[0031] The XRD test of the present invention shows that: NF / Cu-CuS 2 In addition to the characteristic peaks of Ni, NiCoS also contains Cu and CuS. 2 However, except for the characteristic peak of Ni, no relevant characteristic peaks of Ni and Co were detected. The reason is that the obtained compounds of Ni and Co exist in an amorphous form.

[0032] The present invention is tested by EDS and TEM and it is known that: NF / Cu-CuS 2 / NiCoS successfully synthesized uniformly distributed Cu, CuS 2 and NiCoS, and NiCoS exists in an amorphous form.

[0033] The present invention is tested by SEM and found that: NF / Cu-CuS 2 / NiCoS has a hydrangea-like structure, in which the hydrangea layer is composed of Cu-CuS 2 The nanospheres grown on the sheets are composed of NiCoS nanospheres.

[0034] The electrochemical performance test of the present invention shows that: in 1M KOH solution, in the range of 0--1.2V, when the current density is 10mA·cm -2 When NF / Cu-CuS 2 The overpotential of / NiCoS is 39-42mV, and the Tafel slope is 130-136mV·dec -1 At a current density of 10 mA cm -2 , under the condition of a cycle time of 24h, the current retention rate is 95-98%.

[0035] Therefore, the present invention has the following advantages over the prior art:

[0036] 1. In the construction of NF / Cu-CuS 2 When the NiCoS / CuS composite catalyst was used, a crystalline Cu-CuS with a standardized lattice structure was selected. 2 , which makes it have good conductivity and structural stability; amorphous NiCoS with long-range disorder is selected, which makes it have more active sites and an electronic structure more suitable for electrocatalytic hydrogen evolution;

[0037] 2. In the construction of NF / Cu-CuS 2 / NiCoS composite catalyst, the hydrothermal method was first used to synthesize the crystalline Cu-Cu 2 O, and then the electrochemical deposition method was used to deposit the crystalline Cu-Cu 2 O in-situ sulfurization to form crystalline Cu-CuS 2 , and synthesized amorphous NiCoS thereon, forming a composite material of crystalline and amorphous phases;

[0038] 3. NF / Cu-CuS 2 / NiCoS composite catalyst has both crystalline Cu-CuS 2 The amorphous NiCoS has good conductivity, structural stability, abundant active sites and electronic structure that is more suitable for electrocatalytic hydrogen evolution. At the same time, there is also the protection of the composite structure and the synergistic effect between the crystalline and amorphous phases. The existence of this effect enhances their original hydrogen evolution catalytic activity and realizes the design of "1+1>2". BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is the XRD test pattern of Example 1;

[0040] Figure 2 NF / Cu-Cu prepared in Example 1 2 SEM test image of O;

[0041] Figure 3 is the LSV diagram of Example 1;

[0042] Figure 4 The Tafel diagrams of Example 1, Comparative Example 1 and Comparative Example 2 are shown;

[0043] Figure 5 NF / Cu-CuS prepared in Example 1 2 EDS test chart;

[0044] Figure 6 NF / Cu-CuS prepared in Example 1 2 TEM test image;

[0045] Figure 7NF / Cu-CuS prepared in Example 1 2 / SEM test image of NiCoS;

[0046] Figure 8 NF / Cu-CuS prepared in Example 1 2 / SEM test image of NiCoS;

[0047] Fig. 9 This is a stability test diagram of Example 1;

[0048] Fig.10 The XRD test diagrams of Comparative Example 1 and Comparative Example 2 are shown below:

[0049] Fig.11 NF / Cu-CuS prepared in Comparative Example 1 2 SEM test picture;

[0050] Fig.12 LSV diagrams of comparative examples 1 and 2;

[0051] Fig.13 This is the SEM test image of NF / NiCoS prepared in Comparative Example 2. DETAILED DESCRIPTION

[0052] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0053] Example 1

[0054] A method for preparing a crystalline-amorphous composite self-supporting material comprises the following steps:

[0055] Step 1, NF / Cu-Cu 2 Preparation of Cu-O, first, copper sulfate pentahydrate, urea and ammonium fluoride are dissolved in deionized water to obtain a hydrothermal reaction solution with a molar ratio of 2:10:5; then, nickel foam NF is immersed in the hydrothermal reaction solution for hydrothermal reaction at a hydrothermal temperature of 120°C and a hydrothermal time of 6 hours; after the hydrothermal reaction is completed, nickel foam loaded copper / cuprous oxide is obtained by washing and drying, which is referred to as NF / Cu-Cu. 2 O;

[0056] In the step 1, the nickel foam needs to be washed and dried before use. The specific washing and drying conditions are: washing the nickel foam with acetone, hydrochloric acid, deionized water and anhydrous ethanol in sequence, and drying at a drying temperature of 60° C. after washing;

[0057] In order to prove that NF / Cu-Cu 2 O composition, and conduct XRD test. The test results are as follows Figure 1 As shown, NF / Cu-Cu 2 In addition to the characteristic peaks of Ni, O also contains Cu and Cu 2 O characteristic peaks. The test results show that step 1 successfully loaded Cu and Cu on the NF surface 2 O.

[0058] In order to prove that NF / Cu-Cu 2 The microstructure of O was tested by SEM. The test results are as follows Figure 2 As shown, NF / Cu-Cu 2 O is a sheet-like hydrangea structure with a diameter of 10 μm.

[0059] In order to prove that NF / Cu-Cu 2 The electrochemical performance of O was tested. The specific method of the electrochemical performance test is to conduct the electrochemical performance test in a three-electrode system consisting of the material to be tested as the working electrode, the mercuric oxide electrode as the reference electrode, the graphite electrode as the counter electrode, and the 1M KOH solution as the electrolyte.

[0060] In order to prove that NF / Cu-Cu 2 The electrochemical properties of O were tested by LSV. The results are as follows Figure 3 As shown, in the range of 0-1.2V, at a current density of 10mA·cm -2 When NF / Cu-Cu 2 The overpotential of O is 136 mV. The Tafel slope can be calculated by current polarization test. The calculation results are as follows: Figure 4 As shown, NF / Cu-Cu 2 The Tafel slope of O is 140.26 mV·dec -1 .

[0061] Step 2, NF / Cu-CuS 2 / NiCoS preparation, first, nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea are dissolved in deionized water in a molar ratio of 2:4:3:8 to obtain an electrodeposition solution; then, at a current density of 100 mA cm -2 , the electrodeposition time was 20 min, the NF / Cu-Cu obtained in step 1 was 2 O is immersed in an electrochemical deposition solution for electrochemical deposition. After the electrochemical deposition is completed, it is washed and dried to obtain a crystalline-amorphous composite self-supporting material, referred to as NF / Cu-CuS 2 / NiCoS.

[0062] In order to prove that NF / Cu-CuS 2 / NiCoS composition, and conduct XRD test. The test results are as follows Figure 1 As shown, NF / Cu-CuS 2 In addition to the characteristic peaks of Ni, NiCoS also contains Cu and CuS. 2 The test results show that step 2 successfully deposited Cu-Cu on the NF surface. 2 O is sulfided to Cu-CuS 2 However, except for the characteristic peak of Ni, no relevant characteristic peaks of Ni and Co were detected. The reason may be that the obtained compounds of Ni and Co exist in an amorphous form.

[0063] Therefore, in order to further prove that NF / Cu-CuS 2 / NiCoS composition, EDS test and TEM test were carried out.

[0064] EDS test results are as follows Figure 5 As shown, NF / Cu-CuS 2 In addition to Cu and S, NiCoS also contains Ni and Co, and the elements are evenly distributed on the surface of the material. The test results show that through step 2, Ni and Co elements are successfully loaded on the surface of the material.

[0065] TEM test results are as follows Figure 6 As shown, NF / Cu-CuS 2 / NiCoS contains Cu and CuS 2 The characteristic lattice fringes of Cu and CuS 2 It is crystalline and also contains an amorphous region without lattice fringes. Combined with the EDS test results, it can be seen that the amorphous region is composed of Ni, Co and S elements, that is, NiCoS is amorphous.

[0066] The results of EDS and TEM tests show that step 2 successfully prepares nickel cobalt sulfide NiCoS, and it exists in an amorphous form.

[0067] In order to prove that NF / Cu-CuS 2 / NiCoS microstructure, SEM test. The test results are as follows Figure 7 As shown, NF / Cu-CuS 2 The basic microstructure of NiCoS / NiCoS still maintains a flaky hydrangea structure with a diameter of 10 μm. However, the thickness of the micron flower lamella structure increases significantly. Therefore, the SEM test is further magnified. The test results are as follows: Figure 8 As shown, nano-spherical structures with a diameter of 20nm are uniformly grown on the surface of the micron flower layer structure.

[0068] Combining the results of XRD, TEM and EDS tests, we can know that the composition of the nano-spherical structure is NiCoS, referred to as NiCoS nanospheres;

[0069] The Cu-Cu obtained in step 1 is further 2 O combined with the SEM test results, it can be seen that NF / Cu-CuS 2 / NiCoS has a hydrangea-like structure, in which the hydrangea layer is composed of Cu-CuS 2 The nanospheres grown on the sheets are composed of NiCoS nanospheres.

[0070] In order to prove that NF / Cu-CuS 2 / NiCoS electrochemical performance, LSV test. The test results are as follows Figure 3 As shown, in the range of 0-1.2V, at a current density of 10mA·cm -2 When NF / Cu-CuS 2 The overpotential of / NiCoS is 40mV; the Tafel slope can be calculated by current polarization test, and the calculation results are as follows Figure 4 As shown, NF / Cu-CuS 2 The Tafel slope of / NiCoS is 132.53mV·dec -1 Compared with step 1, under the same conditions, NF / Cu-CuS 2 The Tafel slope of Cu-CuS / NiCoS is significantly reduced, indicating that the Cu-CuS prepared by step 3 2 / NiCoS composite structure can accelerate the charge transfer rate, that is, increase the reaction rate and reduce the Tafel slope.

[0071] In order to prove that NF / Cu-CuS 2 / NiCoS stability, and conduct stability performance test. The test results are as follows Fig. 9 As shown, at a current density of 10 mA cm -2 , the current retention rate is 97% under the condition of 24h cycle time. The test results show that NF / Cu-CuS 2 / NiCoS has good stability.

[0072] In order to prove that the components, namely Cu-CuS 2 and the role of NiCoS in the technical solution, provide comparative examples 1 and 2, wherein,

[0073] Comparative Example 1 is that NiCoS is not introduced, that is, the NF / Cu-Cu obtained in step 1 2 Direct sulfurization on O to form NF / Cu-CuS 2 ;

[0074] Comparative Example 2 is that Cu-CuS is not introduced 2 , that is, only NiCoS is prepared on nickel foam.

[0075] Comparative Example 1

[0076] A NF / Cu-CuS 2 The steps not specifically described in the specific steps are the same as those in Example 1, except that in step 2, nickel sulfate hexahydrate and cobalt sulfate heptahydrate are not added, and only thiourea and sodium citrate are added. The obtained material is named NF / Cu-CuS 2 .

[0077] In order to prove that NF / Cu-CuS 2 The composition of the XRD test was carried out. The test results are as follows Fig.10 As shown, NF / Cu-CuS 2 In addition to the characteristic peaks of Ni, Cu and CuS also exist. 2 The test results show that Cu-CuS was successfully prepared on the NF surface. 2 NF / Cu-CuS was successfully prepared 2 .

[0078] In order to prove that NF / Cu-CuS 2 The microstructure of the sample was tested by SEM. The test results are as follows Fig.11 As shown, NF / Cu-CuS 2 Still maintains a nanosheet structure.

[0079] In order to prove that NF / Cu-CuS 2 The electrochemical performance of the LSV test was carried out. The test results are as follows Fig.12 As shown, in the range of 0-1.2V, at a current density of 10mA·cm -2 When NF / Cu-CuS 2 The overpotential is 232mV. The Tafel slope can be calculated by current polarization test. The test results are as follows Figure 4 As shown, NF / Cu-CuS 2 The Tafel slope is 142.53 mV·dec -1 .

[0080] Compared with Example 1, it can be seen that the introduction of amorphous NiCoS can improve the hydrogen evolution performance of the catalyst. The reason is that amorphous NiCoS can react with Cu-CuS 2The composite structure is formed to produce a synergistic effect, which reduces the free energy of the hydrogen evolution reaction. Moreover, after the amorphous NiCoS is combined with the crystalline material, the electronic structure of the interface site can be adjusted, thereby reducing the overpotential of the hydrogen evolution reaction. In addition, by coating the Cu-CuS with amorphous NiCoS 2 , which can prevent Cu-CuS 2 to reduce the shedding of the electrode, thereby improving the cycle stability.

[0081] Comparative Example 2

[0082] A method for preparing NF / NiCoS, wherein the steps not specifically described in the specific steps are the same as the preparation method of Example 1, except that: step 1 is not required, and in step 2, NF is used instead of NF / Cu-Cu 2 O, that is, NF is directly used for step 2, and the obtained material is named NF / NiCoS.

[0083] In order to verify the composition of NF / NiCoS, XRD test was performed. The test results are shown in Fig.10 As shown in the figure, except for the characteristic peak of Ni, no relevant characteristic peaks of Ni and Co were detected. The reason may be that the obtained compounds of Ni and Co exist in an amorphous form.

[0084] Therefore, in order to further prove the composition of NF / NiCoS, the sediment on the surface of NF / NiCoS was tested by XRD alone, and the sediment was referred to as NiCoS. Fig.10 As shown in the figure, NiCoS has a broad diffraction peak of amorphous phase. The test results show that NiCoS exists on the NF surface in amorphous form, that is, NF / NiCoS is successfully prepared.

[0085] In order to verify the microstructure of NF / NiCoS, SEM test was performed. The test results are shown in Fig.13 As shown in Figure 1, NiCoS is directly grown on NF and still maintains a nanosphere structure, but the particle size is uneven, with a diameter of 20-50nm. At the same time, the NiCoS nanospheres are in a disordered and scattered state. 2 , forming a sheet-like hydrangea structure on the NF surface, can make the NiCoS nanospheres evenly distributed on the surface of the micron flower sheet structure, forming an ordered structure and increasing the active area.

[0086] In order to prove the electrochemical performance of NF / NiCoS, LSV test was carried out. The test results are shown in Fig.12 As shown, in the range of 0-1.2V, at a current density of 10mA·cm -2When , the overpotential of NF / NiCoS is 111mV. The Tafel slope can be calculated by current polarization test. The test results are as follows Figure 4 As shown, the Tafel slope of NF / NiCoS is 217.63 mV·dec -1 .

[0087] Compared with Example 1, it can be seen that the introduction of Cu-CuS 2 The formation of a hydrangea-like structure can improve the hydrogen evolution performance of the catalyst. The reason for this is that, combined with the SEM test results, Cu-CuS 2 The microsheets provide active sites for the growth of NiCoS nanospheres, reduce agglomeration, and increase the effective contact area between NiCoS and the electrolyte. 2 Microsheets form synergistic effects for NiCoS nanospheres.

[0088] The following conclusions can be drawn from the above Example 1, Comparative Example 1 and Comparative Example 2:

[0089] 1. After amorphous NiCoS is combined with crystalline materials, the electronic structure of the interface site can be adjusted, thereby reducing the overpotential of the hydrogen evolution reaction;

[0090] 2. Cu-CuS 2 Microsheets can provide active sites for the growth of NiCoS nanospheres, reduce agglomeration, and increase the effective contact area between NiCoS and the electrolyte;

[0091] 3. NiCoS can be combined with Cu-CuS 2 The formation of a composite structure is beneficial to the synergistic effect between the individual components, thereby accelerating the charge transfer between interfaces and improving the hydrogen evolution catalytic performance.

Claims

1. A crystalline-amorphous composite self-supporting material, characterized in that: With nickel foam NF as the substrate, copper sulfate pentahydrate, urea and ammonium fluoride as the raw materials for hydrothermal reaction, NF / Cu-Cu2O was obtained by hydrothermal method, and then nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea were used as the raw materials for electrodeposition, and NF / Cu-CuS2 / NiCoS was obtained by electrochemical deposition.

2. The crystalline-amorphous composite self-supporting material according to claim 1, characterized in that: The NF is used as a self-supporting skeleton; the microscopic morphology of Cu-CuS2 is a hydrangea-like structure with a diameter of 10 μm, that is, the hydrangea layer is composed of Cu-CuS2 micron sheets, and the microscopic morphology of NiCoS is a nano-spherical structure with a diameter of 10 nm; NiCoS nanospheres are grown on the hydrangea-structured sheet; Furthermore, Cu and CuS2 are crystalline, and NiCoS is amorphous.

3. A method for preparing a crystalline-amorphous composite self-supporting material, characterized by comprising the following steps: Step 1, preparation of NF / Cu-Cu2O, first, copper sulfate pentahydrate, urea and ammonium fluoride are dissolved in deionized water to obtain a hydrothermal reaction solution with a certain molar ratio of copper sulfate pentahydrate, urea and ammonium fluoride; then, under certain conditions, nickel foam NF is immersed in the hydrothermal reaction solution for hydrothermal reaction, and after the hydrothermal reaction is completed, nickel foam loaded copper / cuprous oxide is obtained by washing and drying, referred to as NF / Cu-Cu2O; In the step 1, the nickel foam needs to be washed and dried before use. The specific washing and drying conditions are: washing the nickel foam with acetone, hydrochloric acid, deionized water and anhydrous ethanol in sequence, and drying at a drying temperature of 60° C. after washing; Step 2, preparation of NF / Cu-CuS2 / NiCoS, first, nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea are dissolved in deionized water to obtain an electrodeposition solution with nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea satisfying a certain amount of substance ratio; then, under certain conditions, the NF / Cu-Cu2O obtained in step 1 is immersed in the electrodeposition solution for electrochemical deposition, and after the electrochemical deposition is completed, it is washed and dried to obtain a crystalline-amorphous composite self-supporting material, referred to as NF / Cu-CuS2 / NiCoS.

4. The preparation method according to claim 3, characterized in that: In the step 1, the molar ratio of copper sulfate pentahydrate, urea and ammonium fluoride is 2:10:5; In the step 1, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 110-130° C., and the hydrothermal time is 4-6 hours.

5. The preparation method according to claim 3, characterized in that: In the step 2, the molar ratio of nickel sulfate hexahydrate, cobalt sulfate heptahydrate, sodium citrate and thiourea is 2:4:3:8; In step 2, the electrochemical deposition condition is that the current density is 90-100 mA·cm -2 , electrodeposition time 10-20min.

6. The crystalline-amorphous composite self-supporting material according to claim 1, characterized in that: When used as a hydrogen evolution catalyst material, the current density is 10 mA cm in the range of 0-1.2 V. -2 When the overpotential is 39-42mV, the Tafel slope is 130-136mV·dec -1 .

7. The crystalline-amorphous composite self-supporting material according to claim 1, characterized in that: When used as a hydrogen evolution catalyst material, the current density is 10 mA cm -2 , under the condition of a cycle time of 24h, the current retention rate is 95-98%.

Citation Information

Cited By

  • Amorphous / crystalline heterojunction composite material, solid oxide fuel cell and catalyst

    CN121709643A